2018
DOI: 10.1016/j.sjbs.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of verbenalin in rat model of focal cerebral ischemia reperfusion

Abstract: To investigate the protective mechanism of verbenalin on cerebral ischemia-reperfusion injury. Middle cerebral artery occlusion in the left hemisphere was induced in rats by filament insertion, and rat model of focal cerebral ischemia-reperfusion was established. The high, medium and low dose of verbenalin groups were injected in the tail vein of corresponding drugs 10 min before reperfusion, and submitted for 22 h of reperfusion after the operation. Mortality rate was then calculated, and neurological deficit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…Herbal tea made from V. officinalis has traditionally been used for the treatment of insomnia as well as a home remedy for headache, fever, depression, and nervous exhaustion. Verbenalin, one of the major constituents of this plant, has been reported to exhibit sleep-promoting and antioxidant activities [20,22,23]. In our previous study, we have reported relaxation and anti-depressant effects of lemon verbena (Lippia citriodora) extract, rich in verbascoside and verbenalin, both in the in vitro and in vivo models [24].…”
Section: Introductionmentioning
confidence: 98%
“…Herbal tea made from V. officinalis has traditionally been used for the treatment of insomnia as well as a home remedy for headache, fever, depression, and nervous exhaustion. Verbenalin, one of the major constituents of this plant, has been reported to exhibit sleep-promoting and antioxidant activities [20,22,23]. In our previous study, we have reported relaxation and anti-depressant effects of lemon verbena (Lippia citriodora) extract, rich in verbascoside and verbenalin, both in the in vitro and in vivo models [24].…”
Section: Introductionmentioning
confidence: 98%
“…Alleviation of cerebral IR injury through the utilization of effective ingredients in traditional herbal medicine is a promising strategy. 8 Ginkgo biloba L (GB), which belongs to Ginkgoaceae family, is a well-known traditional Chinese medicinal herb, and is widely used for multiple medical purposes. 9 For example, GB is used for the treatment of anxiety, depression, headache, and memory impairment in Europe and Asia.…”
mentioning
confidence: 99%
“…The development of hematoma has led to cognitive impairment, increased Caspase-3 ( Cao et al, 2018 ) and BAX ( Bai et al, 2019 ), level while decreased MBP ( Khan et al, 2006 ) and Bcl-2 ( Keshavarz et al, 2013 ) levels in ALB-treated rats. Moreover, alleviate the elevated oxidative stress AchE ( Ellman et al, 1961 ), LDH ( Mehan et al, 2017 ), MDA ( Mehan et al, 2020 ), nitrite concentration ( Singh et al, 2017 ), and decreased CAT, GSH ( Alam et al, 2020 ), GPx ( Fathimoghadam et al, 2019 ), SOD ( Cai et al, 2015 ) concentration, elevated level of inflammatory cytokines (TNF-α, IL-1β, IL-17) ( Wang et al, 2018 ), decreased neurotransmitters Ach ( Zeng et al, 2017 ), DOPA ( Jamwal and Kumar, 2016 ), GABA, glutamate ( Rajdev et al, 2020 ) in the hemorrhagic brain.…”
Section: Discussionmentioning
confidence: 99%
“…For a consecutive 35 days, the 4-HI administration significantly improves motor and behavioral dysfunction, oxidative damage, neuroinflammation, showing its many target activities in complexes in particular molecular and cellular ways. Caspase-3 and Bax-2 activation associated with cell death and inflammation of neurons caused by cerebral hemorrhages ( Cao et al, 2018 ). Long-term therapy with 4-HI 50 mg/kg and 4-HI 100 mg kg had raised the neurological score in specific behavioral parameters, reflecting its significant neuroprotective role in patients in reducing inflammation and neuronal mortality.…”
Section: Discussionmentioning
confidence: 99%